Optimisation of the elastic track properties of turnout crossings. (February 2016) - Wan, Chang; Markine, Valeri; Shevtsov, Ivan
Rail pads and under sleeper pads (USPs) are resilient elements inserted between the rail and the sleeper, and between the sleeper and the ballast, respectively. They improve the elastic properties of the track's superstructure. In this paper, the approach of estimating the performance of a turnout by using the dynamic forces acting on the crossing as indicators of the extent of crossing nose damage is improved by tuning the stiffness and damping of the rail pads and USPs using a numerical optimisation method. In the optimisation problem, the dynamic forces acting on rails, sleepers and the ballast bed, which should be minimised, are considered in the objective function. Constraints are imposed on the displacements of the structural elements of the turnout crossing. The combined multi-objective optimisation problem is solved using the multipoint approximation method. The results of the optimisation show that application of softer rail pads combined with USPs can significantly reduce the dynamic forces acting on the rails, sleepers and ballast. Moreover, the track elasticity should be varied along the crossing.